Assessing generation y readiness to meet job demand: A case study of internship students at large government invested company - Md Akhir, Romiza; Omar, Mohd Misron; Awadz, Azlina Shaikh; Abdul Hamid, Noor Raihan (2012)
This paper will discuss the survey that was carried out in Large Government Invested Company.Every year, the organization accepted more than 100 internship student placement ranging from various public and private higher learning institutions (HLI) in the country. Those internship students are categorized as generation y.This generation will take over current job position when the baby boomer generation reaches their retirement ages.Survey was conducted to access the readiness of internship students towards job demand.Data were collected through online survey that was developed on the Microsoft SharePoint Portal.The result of the survey will be used to create a profile of future recruitment and developing new working surrounding for generation y in the organization.